Simulating two-dimensional optimal control problem of fractional partial differential equations - Malmir, Iman (Advances in Computational Science and Engineering, 2023)
In this work, a novel method for simulating the fractional two-dimensional linear-quadratic optimal control problem of fractional partial differential equations is introduced. Here, the fractional two-dimensional optimal control problems are transformed into a quadratic programing framework by which we can use many quadratic programming solvers. There is no need to find the optimality conditions and no need to use any multiplier. The optimal control problem involves a two-dimensional performance index and the control of problem depends on both spatial and temporal variables. Some illustrative examples with complicated and challenging situations are investigated.